Visual form discrimination from luminance or disparity cues: functional anatomy by PET. - Gulyás, B; Roland, P; Heywood, C; Popplewell, D; Cowey, A (1994)
With the purpose of elucidating the functional fields involved in the discrimination of visual form based either on luminance or binocular disparity cues, we used PET to measure changes in regional cerebral blood flow (rCBF) in ten volunteers while they performed visual discrimination tasks. The averaged standardized subtraction images (delta rCBF) were analysed for statistically significant changes between the form tasks and their reference tasks. Twenty cortical fields in the visual association areas and the prefrontal cortex were engaged by the discrimination of visual form based upon disparity cues, whereas only four fields showed increased activity during the discrimination of visual form created by luminance cues. The only functional field activated in both conditions was in the left fusiform gyrus. The present findings extend our earlier observations, namely that disparate functional networks of activated fields in the human brain can perform the discrimination of visual form perceptually defined by different visual cues.